Oleanolic acid protection against experimental autoimmune myocarditis modulates the microbiota and the intestinal barrier integrity. (25th November 2020) - Nieto Callejo, M.L; Gallardo, I; Gutierrez, B; Cabero, M.I; Ruiz, L; Alvarez, Y; Simon, I; Calvo, H; Munoz, J.C; Margolles, A; San Roman, J.A; Cachofeiro, V; et al.
Abstract: Background: Autoimmune myocarditis is a cause of dilated cardiomyopathy and heart failure. Recent studies have indicated that leaky gut may allow environmental factors to enter the body and trigger the initiation/development of autoimmune disease. Moreover, there is a growing literature supporting that, beside myocardial fibrosis, a leaky intestinal barrier and gut dysbiosis are pathogenic factors linked to heart failure. The natural triterpene oleanolic acid (OA) has been shown to beneficially influence the severity of the experimental autoimmune myocarditis (EAM), a preclinical model of human myocarditis, via anti-oxidant and immunomodulatory mechanisms. Herein, we investigate gastrointestinal (GI) disturbances and the gut microbiota composition associated with EAM as potential therapeutic target of OA. Methods and results: BALB/c mice were α-myosin-inmunized to induce EAM and treated with OA (25 mg/kg/day, i.p). On day 21, heart fibrosis and parameters related to gut damage such as oxidative stress (O2- ions, lipid peroxidation), gut permeability (D-lactate; I-FABP), inflammation and mucins were determined in serum and/or colon. Fecal microbial profiles were identified by 16S rRNA gene sequencing analysis. Firstly, histological analysis of hearts showed presence of fibrosis (Sirius Red stain) in EAM mice, whereas these effects were not detectable in myocardium from healthy or OA-treated EAM mice. In addition, OA preserved the mucin-containing goblet cells along the colon (Alcian Blue/PAS stain). Consistently, serum levels of the epithelial gut damage markers, including D-lactate and iFABP were significantly reduced in OA treated-EAM mice. The beneficial OA effects also included a decrease in the pro-inflammatory mediators sPLA2-IIA and IL-1β and a protection from the oxidative stress response (DHE stain and TBARS) in serum and colonic tissue of EAM-mice. Furthermore, gut microbiota composition showed a lower bacterial diversity and different relative abundance of certain bacterial taxa in EAM-mice compared to control mice. The families of Muribaculaceae, Lachnospiraceae, and Ruminococcaceae were significantly affected in EAM mice, and only Muribaculaceae recovered levels similar to the healthy-control group, after treatment with OA. Conclusion: Our data show that in addition to the heart, the intestinal barrier and gut microbiota are altered in myocarditis, and that OA treatment could ameliorate this profile. Our data contribute to the idea that gut dysbiosis and GI dysfunction influences myocarditis pathogenesis, and provides new findings regarding the beneficial activity of OA in EAM, suggesting that it may be an interesting candidate to be explored for the treatment of human patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): MINECO, ISCIII, CIBERCV-ISCIII